2014
DOI: 10.1371/journal.pone.0102292
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Apoptotic and Cardioprotective Effects of Salvianolic Acid A on Rat Cardiomyocytes following Ischemia/Reperfusion by DUSP-Mediated Regulation of the ERK1/2/JNK Pathway

Abstract: The purpose of this study was to observe the effects of salvianolic acid A (SAA) pretreatment on the myocardium during ischemia/reperfusion (I/R) and to illuminate the interrelationships among dual specificity protein phosphatase (DUSP) 2/4/16, ERK1/2 and JNK pathways during myocardial I/R, with the ultimate goal of elucidating how SAA exerts cardioprotection against I/R injury (IRI). Wistar rats were divided into the following six groups: control group (CON), I/R group, SAA+I/R group, ERK1/2 inhibitor PD09805… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 31 publications
0
39
1
1
Order By: Relevance
“…Previous studies have demonstrated that oxidative stress induced the activation of MAPK pathways, but there are conflicting reports about their specific effects on oxidative stress [45,46,47]. The ERK pathway is usually thought to deliver survival signals that protect cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that oxidative stress induced the activation of MAPK pathways, but there are conflicting reports about their specific effects on oxidative stress [45,46,47]. The ERK pathway is usually thought to deliver survival signals that protect cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the expression of p-ERK1/2 was increased during IR injury in the myocardium and cerebrum [45,47]. However, Xu et al [46] showed that the expression of p-ERK1/2 in the myocardium in the IR group was not significantly different compared with the control group during IR. In our previous work, crocin activated the p-AKT signaling pathway to inhibit GCL apoptosis in IR rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…This agent is broadly used as a clinical drug to treat cardiovascular diseases [13] . Salvianolic acid A (SAA) ((2R)-3-(3,4-dihydroxyphenyl)-2-[(E)-3-[2-[(E)-2-(3,4-dihy-droxyphenyl)ethenyl]-3,4-dihydroxyphenyl]prop-2-enoyl] oxypropanoic acid) is one of the most bioactive compounds in S miltiorrhiza and exhibits many pharmacological activities, including antioxidation, myocardial protection, antithrombosis, antifibrosis, and the prevention of diabetes complications [14] .…”
Section: Introductionmentioning
confidence: 99%
“…DUSP4 is an inducible nuclear phosphatase whose substrates include all three of the MAPKs (ERK, JNK and p38) and it has been demonstrated to be important for cardiovascular function [16, 21-26]. Overexpression of DUSP4 in human endothelial cells enhances adhesion molecule expression and protects against apoptosis [22].…”
Section: Introductionmentioning
confidence: 99%